Lithium ion battery negative electrode material coating agent and preparation method and application thereof
By using a mixing and dispersion method of asphalt powder and conductive material in the lithium-ion battery negative electrode material coating agent, and mechanical blending in an oxygen-containing gas atmosphere, the problems of uneven coating and poor conductivity are solved, and the negative electrode material excellent conductivity, low impedance and good rate performance are achieved.
Patent Information
- Application Number
- CN202311340773.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-18
AI Technical Summary
The existing lithium-ion battery negative electrode material coating technology has problems such as uneven coating, poor conductivity, poor rate performance and high impedance.
By mixing and dispersing methods of asphalt powder and conductive materials, mechanical blending is performed in an oxygen-containing gas atmosphere to prepare a coating agent with excellent conductivity, low impedance and good rate performance.
The uniform coating of the negative electrode material is achieved, which significantly improves the conductivity, rate performance and cycling characteristics, and reduces the material surface resistance.
Smart Images

Figure BDA0004497193840000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a coating agent for a negative electrode material of a lithium ion battery, a preparation method thereof and an application thereof. Background Art
[0002] As the most widely used negative electrode material, graphite has the advantages of abundant reserves, low price, stable electrochemical performance, and actual energy density close to theoretical energy density. However, graphite also has obvious disadvantages, such as poor compatibility with electrolyte and easy peeling of graphite layer during lithium insertion, which leads to poor cycle performance. Based on the above disadvantages, graphite needs to be modified, such as coating, to ensure cycle performance and initial charge and discharge efficiency.
[0003] Coating and modifying graphite is one of the effective methods to improve the electrochemical performance of graphite negative electrode materials. However, during the coating process, as the solvent evaporates, the resin coated on the surface of the spherical graphite tends to become uneven, with some graphite particles coated thicker and some graphite particles coated thinner, resulting in a poor coating effect and a corresponding increase in the surface resistance of the material. Therefore, it is urgent to improve the existing coating technology to obtain a negative electrode material with more uniform coating, better rate performance and low impedance.
[0004] Patent application CN202011412892.8 discloses a coating agent, a modified graphite material, and a preparation method and application thereof, wherein the coating agent components in the lithium-ion battery are coumarone resin and washing oil, which are modified and mixed with graphite and carbonized to prepare the modified graphite material.
[0005] Patent application CN106469814A discloses a coating agent, a negative electrode material, a lithium-ion battery, and a preparation method and application thereof, wherein the coating agent is prepared by mixing graphene, a water-insoluble precursor, and a dispersant, and then mixed with a graphite material and carbonized to prepare a lithium battery negative electrode material.
[0006] Patent application CN107482203A discloses a coating modification method of graphite negative electrode material, graphite negative electrode material and application, which mixes graphite and asphalt through liquid phase coating.
[0007] Patent application CN109913253A discloses a special asphalt for lithium battery coating and a preparation method. This method requires a lot of purification work and uses various solvents for extraction. The quality is not easy to control, and there is no conductive agent component, so the resistance value is large.
[0008] Patent application CN202011412892.8 discloses a coating agent, a modified graphite material, and its preparation method, application and lithium-ion battery. The preparation method of the coated asphalt provided is relatively complicated, and the surface of the material cannot form an overall network.
[0009] Patent application CN106469814A discloses a coating agent, a negative electrode material, a lithium-ion battery and a preparation method thereof. The application process thereof is relatively complicated, and graphene is prone to agglomeration, uneven coating, poor stability, and easy introduction of other impurities.
[0010] Patent application CN107482203A discloses a coating modification method for graphite negative electrode materials, graphite negative electrode materials and applications. The coating process of this method is complicated, which easily causes uneven coating and poor stability. Summary of the invention
[0011] In view of this, the present invention provides a lithium ion battery negative electrode material coating agent and a preparation method and application thereof. The coating agent obtained based on the method of the present invention is used for coating negative electrode conductive materials, especially graphite materials. It can be well compatible with negative electrode conductive materials such as graphite, which is conducive to more uniform coating of negative electrode conductive materials, thereby obtaining a negative electrode material with excellent conductivity, low impedance and good rate performance.
[0012] To achieve the purpose, the present invention provides the following technical solutions:
[0013] In one aspect, the present invention provides a method for preparing a coating agent for a negative electrode material of a lithium ion battery, the preparation method comprising the following steps:
[0014] 1) Mixing and dispersing the asphalt powder and the conductive material uniformly; wherein, based on the total mass of the asphalt powder and the conductive material, the proportion of the conductive material is 0.1%-8%; specifically, the mixing operation of this step can be performed in a high-speed mixer;
[0015] 2) Mechanically blending the mixed material obtained in step 1) in the presence of an oxygen-containing gas, wherein the mechanical blending is performed at a temperature of 120-280° C. for a blending time of more than 6 hours, preferably 6-120 hours; the volume percentage of oxygen in the oxygen-containing gas is 30-90%;
[0016] 3) The material obtained in step 2) is crushed to obtain a coating agent.
[0017] When preparing the coating agent, the present invention preliminarily mixes the asphalt and the conductive material, and then mechanically blends them in a gas atmosphere containing 30-90% oxygen at a temperature of 120-280°C for more than 6 hours, which is conducive to making the conductive material, especially the nano conductive material, uniformly dispersed in the system, and obtaining a coating agent with good conductivity. The obtained coating agent has good compatibility with conductive materials such as graphite, and can more uniformly coat conductive materials such as graphite, which is conducive to improving the electrical properties of the negative electrode material, such as the conductivity, rate performance and cycle characteristics. The scheme of the present invention can especially overcome the problem that it is difficult to uniformly disperse the nano conductive material when preparing the coating agent, and thus it is difficult to obtain a coating agent with good performance.
[0018] In the process of preparing the coating agent, the present invention does not need to introduce additional catalysts, initiators and other reagents, and can obtain a coating agent with good dispersion of various components, good conductivity and excellent compatibility with graphite. The process is simple and the required reagent types are small.
[0019] In some embodiments, in step 1), the particle size D50 of the asphalt powder is 50 μm-300 μm.
[0020] In some embodiments, in step 3), the particle size D50 of the coating agent is 2-10 μm.
[0021] Specifically, in step 2), the remaining gas in the oxygen-containing gas is a protective gas, and the protective gas is, for example, one or more of nitrogen, argon, helium,
[0022] In some embodiments, in step 1), the asphalt powder is selected from one or more of mesophase asphalt, coal asphalt, petroleum asphalt, and oxidized asphalt. Preferably, the softening point of the asphalt powder is 100-300°C, preferably 120-300°C;
[0023] Preferably, the conductive material in step 1) is a nano conductive material, and the nano conductive material is selected from one or more of carbon nanotubes (CNT), graphene, vapor phase carbon fiber (VGCF), and conductive carbon black. The coating agent preparation process in the prior art based on the nano conductive material has the problem of being difficult to disperse uniformly. The preparation method of the present invention can solve this problem well, and can make the nano conductive material well dispersed in the coating agent, thereby obtaining a coating agent with excellent performance.
[0024] In some embodiments, the mechanical shear blending in step 2) is carried out in a kneader, an extruder, a roller press or a ball mill; in some embodiments, the step 2) is carried out in the kneader, preferably, the temperature is controlled to be 120-280°C, the rotation speed is 200-300 rpm, and the processing time is 96-120h; in some embodiments, the step 2) is carried out in the ball mill, preferably, the rotation speed is controlled to be 400-800 rpm, the revolution speed is 50-200 rpm, the temperature is 120-280°C, and the ball milling time is 30-100h; in some embodiments, the step 2) is carried out in the extruder, preferably, the rotation speed is controlled to be 100-400 rpm, the temperature is 120-300°C, and the processing time is 6-90h; in some embodiments, the step 2) is carried out in the roller press, preferably, the temperature is controlled to be 120-280°C, and the processing time is 8-60h. Carrying out the mechanical blending in step 2) under the above preferred conditions can better disperse the nano-conductive material evenly, avoid agglomeration of the nano-conductive material, obtain a better dispersion effect, and help further improve the electrochemical properties of the coating agent.
[0025] In the coating agent preparation method of the present invention, mechanical blending is carried out at 120-280°C in a gas atmosphere containing 30-90% oxygen, which can achieve shear and melt blending of materials, and the nano-conductive material and the asphalt material have good wettability. The asphalt material can be well oxidized without the need to add other reagents such as catalysts, and the various components can be well and evenly dispersed, so that the nano-conductive material can be more evenly dispersed in the system. At a relatively low dosage of nano-conductive material, a coating agent with good conductivity can be obtained, and the obtained coating agent has good compatibility with graphite material. The coating agent of the present invention is used for coating treatment of graphite material, which can significantly improve the electrochemical properties such as rate performance and capacity of the negative electrode material.
[0026] In the method for preparing the coating agent of the present invention, the amount of nano-conductive material used is 0.1%-8% of the total mass of the asphalt powder and the nano-conductive material, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 7%, 8%, etc. The present invention does not need to introduce a higher amount of nano-conductive material to obtain a coating agent with good conductivity, which is beneficial to reducing the homogenization time and improving the overall performance of the material.
[0027] The present invention also provides a coating agent for a negative electrode material of a lithium ion battery, which is prepared by the preparation method described above. The coating agent prepared by the preparation method of the present invention has good conductivity; in some embodiments, the conductivity of the coating agent prepared by the present invention is tested by a powder resistance meter, and its resistivity is between 0.05 and 20 MΩ, for example, the resistance range is 0.2 to 12 MΩ; the material density is 0.8 to 1.8 g / cm3 , for example, the density range is 1.0~1.7g / cm 3 ; The coking value range is 50 to 80%, for example, the coking value range is 50 to 70%.
[0028] The present invention also provides a negative electrode material for a lithium ion battery, the negative electrode material comprising a negative electrode conductive material and a coating agent, the coating agent being a coating agent obtained by the preparation method described above. Furthermore, the negative electrode conductive material is a graphite material, which may be a natural graphite material or an artificial graphite material. The coating agent provided by the present invention has good electrical conductivity and is well compatible with the graphite material. The graphite material is coated with the coating agent of the present invention, and the graphite material can be coated more evenly, and the electrochemical properties of the negative electrode material, such as the conductive performance, rate performance and cycle characteristics, can be improved. The negative electrode material obtained by coating the graphite conductive material with the coating agent of the present invention has a higher electrical conductivity.
[0029] In some embodiments, based on the total mass of the coating agent and the negative electrode conductive material, the coating agent accounts for 2-10%, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0030] The present invention also provides a method for preparing the negative electrode material described above, the method comprising the following steps:
[0031] The coating agent and the negative electrode conductive material are mixed uniformly, and carbonized under an inert atmosphere, the carbonization temperature is preferably 1000-1300°C, and the carbonization time is preferably 2-6 hours; after carbonization, the mixture is broken up and sieved. Specifically, conventional demagnetization operations may also be included. Specifically, the aforementioned inert atmosphere may be provided by gases such as nitrogen and argon.
[0032] Furthermore, when the coating agent and the negative electrode conductive material are mixed uniformly, they can be solid mixed or melt mixed, wherein "solid mixed" means directly mixing the solid components.
[0033] The present invention also provides a negative electrode for a lithium ion battery, wherein the negative electrode for the lithium ion battery comprises the negative electrode material described above or comprises the negative electrode material prepared by the preparation method described above.
[0034] The technical solution provided by the present invention has the following beneficial effects:
[0035] The coating agent provided by the present invention can overcome the problems of uneven coating and poor conductivity caused by the coating layer being an amorphous carbon layer when the coating agent of the prior art is coated on the graphite material, resulting in defects such as poor conductivity, poor rate performance, and high impedance of the obtained negative electrode material; the coating agent prepared by the present invention has lower resistance, higher density and coking value. The coating agent of the present invention is used to coat the graphite negative electrode material, which can significantly improve the electrochemical properties of the graphite material, and is conducive to obtaining a negative electrode material with better rate performance, cycle characteristics and first effect.
[0036] The coating agent prepared by the preparation method of the present invention can evenly disperse the conductive material, especially the nano conductive material, in the asphalt. The novel coating agent prepared by the present invention can form a conductive network, and when used for coating graphite negative electrode materials, it can significantly improve the interface impedance of the graphite negative electrode materials, effectively reduce the surface resistance of the materials, and improve the cycle stability, rate performance and first effect of the materials. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs. Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0039] Test method description:
[0040] Coking value: Tested in accordance with national standard GB / T 2290-2012.
[0041] Ingredients Description:
[0042] Coal tar pitch: from Xuyang Chemical; mesophase asphalt: from Jining Chenxing; petroleum asphalt: from Jinzhou Petrochemical; carbon nanotubes: from Jiangsu Tiannai Technology; artificial graphite: from Shenzhen Beite; vapor-phase carbon fiber (VGCF): Shanghai Zhaoyuan Industrial Co., Ltd.; graphene: Jiangsu Tanfeng Technology; conductive carbon black: Cabot Corporation, USA.
[0043] Example 1
[0044] The preparation steps of the coating agent are as follows:
[0045] 1) Grind coal tar (softening point is 180°C) and sieve to obtain particles with a particle size D50 of 100 microns, add carbon nanotubes (the amount of carbon nanotubes is 2% of the total mass of carbon nanotubes and coal tar); mix the materials in a mixer for 8 hours; the carbon nanotubes used have an aspect ratio of 100 and a particle size of 5 nm;
[0046] 2) The mixed material obtained in step 1) is mechanically blended in a kneader at a rotation speed of 200 revolutions per minute (rpm), a treatment temperature of 160° C., and a treatment time of 120 hours. During the treatment process, a gas having an oxygen volume content of 40% and the rest being nitrogen is introduced.
[0047] 3) After the treatment, the product is cooled and then crushed to obtain a coating agent with a D50 controlled at 4 μm.
[0048] The powder resistivity of the coating agent prepared above was tested, and its resistivity was 8MΩ; the density of the coating agent was 1.3g / cm 3 , the coking value is 51%.
[0049] Preparation of negative electrode materials:
[0050] Artificial graphite was used as the raw material, the coating agent prepared above was added (the amount was 3% of the total mass of artificial graphite and the coating agent), mixed in a VC mixer for 30 minutes, and then carbonized at 1000°C for 3 hours under a nitrogen atmosphere; then cooled, broken up and passed through a 300-mesh sieve to obtain a negative electrode material.
[0051] The conductivity of the obtained negative electrode material was tested and found to be 1.5*10 -4 Ω*cm 2 , the Id / Ig tested by Raman was 0.35.
[0052] Preparation of lithium-ion battery negative electrode:
[0053] The above-mentioned negative electrode material is mixed with carbon black, polyvinylidene fluoride (PVDF) and NMP (N-methylpyrrolidone) in a mass ratio of negative electrode material: carbon black: PVDF: NMP = 92:3:5:200, stirred evenly and then coated on copper foil, and dried in a vacuum oven at 120°C for 12 hours to obtain a lithium ion battery negative electrode.
[0054] The prepared lithium-ion battery negative electrode was subjected to electrochemical performance testing, and the experimental results are shown in Table 1.
[0055] Example 2
[0056] The preparation steps of the coating agent are as follows:
[0057] 1) Crush and sieve the mesophase pitch (softening point of 200°C) to obtain a granular powder with a particle size D50 of 75 microns, add VGCF (VGCF accounts for 3% of the total mass of the mesophase pitch and VGCF), and mix the materials evenly in a mixer for 6 hours; the VGCF used has an aspect ratio of 70 and a particle size of 5 nm;
[0058] 2) The mixture obtained in step 1) is mechanically ground in a ball mill at a rotation speed of 800 rpm, a revolution speed of 200 rpm, and a temperature of 240° C. for 60 hours. During the ball milling process, a gas with a volume content of 60% oxygen and the rest argon is introduced.
[0059] 3) After the treatment, the product is cooled and then crushed to obtain a coating agent with a D50 controlled at 3 μm.
[0060] The powder resistivity of the coating agent prepared above was tested, and its resistivity was 2MΩ; the density of the coating agent was 1.5g / cm 3 , the coking value is 60%.
[0061] Preparation of negative electrode materials:
[0062] Artificial graphite was used as the raw material, the above-mentioned coating agent was added (the amount was 3% of the total mass of artificial graphite and the coating agent), mixed in a VC mixer for 30 minutes, and then carbonized at 1100°C for 3 hours under a nitrogen atmosphere, then cooled, broken up and passed through a 300-mesh sieve to obtain a negative electrode material.
[0063] The conductivity of the obtained negative electrode material was tested and found to be 0.9*10 -5 Ω*cm 2 , the Id / Ig tested by Raman was 0.45.
[0064] Preparation of lithium-ion battery negative electrode:
[0065] The negative electrode material was mixed with carbon black, polyvinylidene fluoride (PVDF) and NMP in a mass ratio of negative electrode material: carbon black: PVDF: NMP = 92:3:5:200, stirred evenly and coated on copper foil, and dried in a vacuum oven at 120°C for 12 hours to obtain a lithium ion battery negative electrode.
[0066] The prepared lithium-ion battery negative electrode was subjected to electrochemical performance testing, and the experimental results are shown in Table 1.
[0067] Example 3
[0068] The preparation steps of the coating agent are as follows:
[0069] 1) A mixture of petroleum asphalt and coal asphalt (mixed in a mass ratio of 1:1) is used as an asphalt raw material (the softening point after mixing is 180°C), which is crushed and sieved to obtain a granular powder with a particle size D50 of 75 microns, and graphene (accounting for 8% of the total mass of the asphalt raw material and graphene) is added, and mixed in a mixer for 8 hours to make the materials uniformly mixed; the particle size of the graphene used is 5 microns and the thickness is 10nm;
[0070] 2) The mixed material obtained in step 1) is mechanically blended in an extruder at a rotation speed of 400 revolutions per minute (rpm), a treatment temperature of 200° C., and a treatment time of 64 hours. During the treatment process, a gas having an oxygen volume content of 80% and the rest being nitrogen is introduced.
[0071] 3) After the treatment, the product is cooled and then crushed to obtain a coating agent with a D50 controlled at 3 μm.
[0072] The powder resistivity of the coating agent prepared above was tested, and its resistivity was 0.6MΩ; the density of the coating agent was 1.7g / cm 3 , the coking value is 60%.
[0073] Preparation of negative electrode materials:
[0074] Artificial graphite was used as the raw material, and the coating agent prepared above was added (the amount was 5% of the total mass of artificial graphite and the coating agent), heated to 500°C in a coating kettle for melt mixing for 30 minutes, and then kept at 1000°C for 3 hours under a nitrogen atmosphere for carbonization; then cooled, broken up and passed through a 300-mesh sieve to obtain a negative electrode material.
[0075] The conductivity of the obtained negative electrode material was tested and found to be 3.5*10 -5 Ω*cm 2 , the I d / I g tested by Raman is 0.32.
[0076] Preparation of lithium-ion battery negative electrode:
[0077] The negative electrode material was mixed with carbon black, polyvinylidene fluoride (PVDF) and NMP in a mass ratio of negative electrode material: carbon black: PVDF: NMP = 92:3:5:200, stirred evenly and coated on copper foil, and dried in a vacuum oven at 120°C for 12 hours to obtain a lithium ion battery negative electrode.
[0078] The prepared lithium-ion battery negative electrode was subjected to electrochemical performance testing, and the experimental results are shown in Table 1.
[0079] Example 4
[0080] The preparation steps of the coating agent are as follows:
[0081] 1) Crush and sieve petroleum asphalt (softening point is 200°C) to obtain particles with a particle size D50 of 48 microns, add conductive carbon black (the amount of conductive carbon black is 5% of the total mass of conductive carbon black and petroleum asphalt), and mix the materials evenly in a mixer for 10 hours. The particle size of the conductive carbon black used is 25nm.
[0082] 2) The mixed material obtained in step 1) is mechanically blended in a kneader at a rotation speed of 300 revolutions per minute (rpm), a treatment temperature of 210° C., and a treatment time of 96 hours. During the treatment process, a gas with a volume content of 60% oxygen is introduced, and the rest is 20% nitrogen and 20% argon.
[0083] 3) After the treatment, the product is cooled and then crushed to obtain a coating agent with a D50 controlled at 3 μm.
[0084] The powder resistivity of the coating agent prepared above was tested, and its resistivity was 12MΩ; the density of the coating agent was 1.5g / cm 3 , the coking value is 55%.
[0085] Preparation of negative electrode materials:
[0086] Artificial graphite was used as the raw material, the coating agent prepared above was added (the amount was 5% of the total mass of artificial graphite and the coating agent), mixed in a VC mixer for 30 minutes, and then carbonized at 1000°C for 3 hours under a nitrogen atmosphere; then cooled, broken up and passed through a 300-mesh sieve to obtain a negative electrode material.
[0087] The conductivity of the obtained negative electrode material was tested and found to be 5.2*10 -4 Ω*cm 2 , the I d / I g tested by Raman is 0.25.
[0088] Preparation of lithium-ion battery negative electrode:
[0089] The negative electrode material was mixed with carbon black, polyvinylidene fluoride (PVDF) and NMP in a mass ratio of negative electrode material: carbon black: PVDF: NMP = 92:3:5:200, stirred evenly and coated on copper foil, and dried in a vacuum oven at 120°C for 12 hours to obtain a lithium ion battery negative electrode.
[0090] The prepared lithium-ion battery negative electrode was subjected to electrochemical performance testing, and the experimental results are shown in Table 1.
[0091] Comparative Example 1 (Compared with Example 4)
[0092] The same method is used as in Example 4, except that when preparing the coating agent, step 2) is performed in an air atmosphere. The remaining operations are performed as in Example 4.
[0093] The coating agent prepared in Comparative Example 1 was subjected to a powder resistivity test, and its resistivity was infinite; the density of the coating agent was 1.1 g / cm 3 , the coking value is 35%.
[0094] Preparation of negative electrode materials:
[0095] Take artificial graphite as raw material, add the above-mentioned coating agent (the amount is 5% of the total mass of artificial graphite and coating agent), mix in a VC mixer for 30 minutes, and then carbonize at 1000°C for 3 hours under nitrogen atmosphere; then cool and break through a 300-mesh sieve to obtain a negative electrode material.
[0096] The conductivity of the obtained negative electrode material was tested and found to be 5.2*10 -3 Ω*cm 2 , the Id / Ig tested by Raman was 0.12.
[0097] Preparation of lithium-ion battery negative electrode:
[0098] The negative electrode material was mixed with carbon black, polyvinylidene fluoride (PVDF) and NMP in a mass ratio of negative electrode material: carbon black: PVDF: NMP = 92:3:5:200, stirred evenly and coated on copper foil, and dried in a vacuum oven at 120°C for 12 hours to obtain a lithium ion battery negative electrode.
[0099] The prepared lithium-ion battery negative electrode was subjected to electrochemical performance testing, and the experimental results are shown in Table 1.
[0100] Comparative Example 2 (Compared with Example 4)
[0101] The method is carried out in accordance with Example 4, except that: when preparing the coating agent, in step 1), the amount of conductive carbon black used is 10% of the total mass of conductive carbon black and petroleum asphalt; and step 2) is carried out in an air atmosphere. The remaining operations are carried out in accordance with Example 4. The coating agent prepared in Comparative Example 2 is subjected to a powder resistivity test, and its resistivity is 30MΩ; the density of the coating agent is 0.9g / cm 3 , the coking value is 40%.
[0102] Preparation of negative electrode materials:
[0103] Take artificial graphite as raw material, add the above-mentioned coating agent (the amount is 5% of the total mass of artificial graphite and coating agent), mix in a VC mixer for 30 minutes, and then carbonize at 1000°C for 3 hours under nitrogen atmosphere; then cool and break through a 300-mesh sieve to obtain a negative electrode material.
[0104] The conductivity of the obtained negative electrode material was tested and found to be 5.2*10 -4 Ω*cm2 , the Id / Ig tested by Raman was 0.20.
[0105] Comparative Example 3 (Compared with Example 3)
[0106] The method was carried out in accordance with Example 3, except that when preparing the coating agent, during the mechanical blending in step 2), the gas composition introduced was: oxygen with a volume content of 5%, and the rest was nitrogen. The remaining operations were carried out in accordance with Example 3.
[0107] The powder resistivity of the coating agent prepared above was tested, and its resistivity was 120MΩ; the density of the coating agent was 1.0g / cm 3 , the coking value is 30%.
[0108] Referring to Example 3, the coating agent prepared in Comparative Example 3 was prepared into a negative electrode material.
[0109] The conductivity of the obtained negative electrode material was tested and found to be 3.5*10 -2 Ω*cm 2 , the Id / Ig tested by Raman was 0.15.
[0110] Comparative Example 4 (Compared with Example 2)
[0111] The same method was used as in Example 2, except that the mechanical grinding in step 2) was performed at room temperature when preparing the coating agent. The remaining operations were performed as in Example 2.
[0112] The coating agent prepared in Comparative Example 4 was subjected to a powder resistivity test, and its resistivity was infinite; the density of the coating agent was 1.1 g / cm 3 , the coking value is 35%.
[0113] Preparation of negative electrode materials:
[0114] Artificial graphite was used as the raw material, the above-mentioned coating agent was added (the amount was 3% of the total mass of artificial graphite and the coating agent), mixed in a VC mixer for 30 minutes, and then carbonized at 1100°C for 3 hours under a nitrogen atmosphere, then cooled, broken up and passed through a 300-mesh sieve to obtain a negative electrode material.
[0115] The conductivity of the obtained negative electrode material was tested and found to be 0.9*10 -3 Ω*cm 2 , the Id / Ig tested by Raman was 0.15.
[0116] Preparation of lithium-ion battery negative electrode:
[0117] The negative electrode material was mixed with carbon black, polyvinylidene fluoride (PVDF) and NMP in a mass ratio of negative electrode material: carbon black: PVDF: NMP = 92:3:5:200, stirred evenly and coated on copper foil, and dried in a vacuum oven at 120°C for 12 hours to obtain a lithium ion battery negative electrode.
[0118] The prepared lithium-ion battery negative electrode was subjected to electrochemical performance testing, and the experimental results are shown in Table 1.
[0119] Table 1
[0120]
[0121] Note: If there is any inconsistency between the data in the table and the previous description, the previous description shall prevail.
[0122] It can be seen from the above experimental results that the coating agent prepared by the preparation method of the present invention has a lower resistivity, a higher density and a higher coking value; the negative electrode material obtained based on the coating agent prepared by the present invention has better electrochemical properties, a lower conductivity and a higher Id / Ig value; and thus is beneficial to improve the electrochemical properties of the battery negative electrode, with higher first efficiency, reversible capacity and rate performance.
[0123] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A method for preparing a coating agent for a negative electrode material of a lithium ion battery, characterized in that: The preparation method comprises the following steps: 1) Mixing and dispersing the asphalt powder and the conductive material uniformly; wherein, based on the total mass of the asphalt powder and the conductive material, the proportion of the conductive material is 0.1%-8%; 2) Mechanically blending the mixed material obtained in step 1) in the presence of an oxygen-containing gas, wherein the mechanical blending is performed at a temperature of 120-280° C. for a blending time of more than 6 hours, preferably 6-120 hours; the volume percentage of oxygen in the oxygen-containing gas is 30-90%; 3) The material obtained in step 2) is crushed to obtain a coating agent.
2. The preparation method according to claim 1, characterized in that: In step 1), the particle size D50 of the asphalt powder is 50 μm-300 μm; And / or, in step 3), the particle size D50 of the coating agent is 2-10 μm; And / or, in step 2), the rest of the gas in the oxygen-containing gas is a protective gas, and the protective gas is, for example, one or more of nitrogen, argon, and helium.
3. The preparation method according to claim 1, characterized in that: In step 1), the asphalt powder is selected from one or more of mesophase asphalt, coal asphalt, petroleum asphalt, and oxidized asphalt; preferably, the softening point of the asphalt powder is 100-300°C, preferably 120-300°C; And / or, in step 1), the conductive material is a nano conductive material, preferably, the nano conductive material is selected from one or more of carbon nanotubes, graphene, vapor phase carbon fiber, and conductive carbon black.
4. The preparation method according to any one of claims 1 to 3, characterized in that The step 2) is carried out in a kneader, an extruder, a roller press or a ball mill; Preferably, the step 2) is carried out in the kneader, the temperature is controlled at 120-280° C., the rotation speed is 200-300 rpm, and the processing time is 96-120 h; Preferably, the step 2) is carried out in the ball mill, the rotation speed is controlled to be 400-800 rpm, the revolution speed is controlled to be 50-200 rpm, the temperature is controlled to be 120-280° C., and the ball milling time is controlled to be 30-100 h; Preferably, the step 2) is carried out in the extruder, with the speed controlled at 100-400 rpm, the temperature at 120-280° C., and the processing time at 6-90 h; Preferably, the step 2) is carried out in the roller press, the temperature is controlled at 120-280° C., and the processing time is 8-60 hours.
5. A coating agent for negative electrode material of lithium ion battery, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 4.
6. A negative electrode material for a lithium ion battery, characterized in that: The negative electrode material comprises a negative electrode conductive material and a coating agent, and the coating agent is a coating agent prepared by the preparation method according to any one of claims 1 to 4.
7. The negative electrode material according to claim 6, characterized in that The negative electrode conductive material is graphite material.
8. The negative electrode material according to claim 6 or 7, characterized in that: Based on the total mass of the coating agent and the negative electrode conductive material, the coating agent accounts for 2-10%.
9. The method for preparing the negative electrode material according to any one of claims 6 to 8, characterized in that: The preparation method comprises the following steps: The coating agent and the negative electrode conductive material are mixed uniformly, and carbonized in an inert atmosphere. The carbonization temperature is preferably 1000-1300° C., and the carbonization time is preferably 2-6 hours. After carbonization, the mixture is broken up and sieved.
10. A negative electrode for a lithium ion battery, characterized in that: The negative electrode of the lithium-ion battery includes the negative electrode material according to any one of claims 6 to 8 or includes the negative electrode material prepared by the preparation method according to claim 9.
Citation Information
Patent Citations
Coating agent, anode material, lithium ion battery and preparation method thereof
CN106469814A
Graphite cathode material coating modification method, graphite cathode material and application
CN107482203A
Special asphalt for lithium battery coating and preparation method
CN109913253A
Coating agent, modified graphite material, preparation method and application of modified graphite material, and lithium ion battery
CN112670469A